Subjective body and didactics: Practical construction - Ayala Zuluaga, Jose Enver; Arboleda Gomez, Rubiela; Neto, Samuel de Souza [UNESP] (Univ La Gran Colombia, 2016)
This article deals with findings of the category Subjective body and didactics: practical construction of the study named senses that teachers give to motor skills, as an ability for teaching, a study constituted from the need to review other understandings in education and in teachers training. The central objective was prepared in order to unveil the expressions of education actors, parting from the interpretation on them in a didactic key; such process used the comprehensive approach of the research under the research type named reflective ethnography, the work led to define as discussion axles the categories Body and didactics: origin of the transit, I incorporate and teach, and the body-perception-thought, which express and conclude which express and conclude that configurations of the subjects that transit the classroom bear practical anchorages to improve teaching-learning processes, as they are guided by the realities provided by the classroom, and which do not have a condition other than what refers to existence of the classroom actors.
Keywords: Subjective body; didactics; perception and teacher training